Copyright Commercialization of Songs Uploaded in TikTok Application Without the Creator’s Permission - Fakhira Meshara Salsabila; Ranti Fauza Mayana; Laina Rafianti (LPPM Universitas Jambi, 2021)
TikTok has now become an application that is widely used by all people and that it has become a trend. The application has a General Terms of Services which is the basis for using Tiktok. In the practice of uploading songs by users without realizing it, gives a juridical implication because users do not fully understand the provisions contained in the Terms of Services. Appropriately, before the user takes and modifies the work of the song which is then used for commercial use, the user already has a license or permission from the author. The problems studied are the legal consequences of uploading songs in this TikTok application which are commercialized without the permission of the Creator by the related users, as well as to see the legal efforts that can be taken by the Creator on songs that are commercialized without the permission of the Creator in this application. The research method used is juridical normative, namely an approach method that uses laws and legal principles as a means of solving the problems at hand. The results of the research conclude that currently, the violation of Copyright has changed from criminalization to remuneration, where the legal consequence of the Copyright infringement is non-compensation to the Creator due to commercial use of songs. Regarding the protection efforts, it can be done in several ways, namely recording, administrative legal remedies and supervision. In terms of fulfilling the rights of the Creator, legal remedies can be taken, namely preventive and repressive measures consisting of civil and criminal remedies. In addition, it can also be resolved by alternative dispute resolution and arbitration.